The Effectiveness of Ginger In Reducing Nausea And Vomiting In Pregnant Women In Health Centers Trimester I Dolok Masihul District Dolok masihul KabSerdang Bedagai - FITRIA, RAHMI (Jurnal Martenity and Neonatal, 2013)
Approximately 50% of pregnant women experience nausea and vomiting up. This happened the first 12 weeks of pregnancy, usually disappears by the end of that time, but sometimes appears towards the end of pregnancy. Most nausea occurs in the morning, so-called morning sickness, it may also occur at any time. Pregnant women are reduced thanks to the ginger nausea, without harmful side effects.